Hypersensitivity pneumonitis in Türkiye: An underrecognized pulmonary disorder - Uzun, Oguz; Adıguzel Gundogdu, Busra; Sullu, Yurdanur; Topcu Erturk, Kader; Kement, Sümeyye; Selen Ala Cıtlak, Fatma (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
Introduction: The aims of this study are (1) to investigate hypersensitivity pneumonitis (HP) related publications from Türkiye, (2) to discuss features of HP concerning our case series, and (3) to evaluate our patients in terms of diagnostic confidence according to guidelines.Methods: We conducted a comprehensive review of the literature to analyse cumulated data about HP publications originating from Türkiye. HP cases diagnosed and followed in last 5 year in our hospital were also evaluated.Results: There are 34 Türkiye-originated HP-related publication. 13 articles were of pediatric origin and 19 of the articles included adult patients. Bird fancier’s disease was the most frequent etiology of HP.  A total of 138 patients were included in this study. 107 (77.5%) patients were female and 31 (22.5%) were male. A definite diagnosis has been made to 45 (33%) patients according to the ATS  guideline and to 94 (68%) patients according to the ACCP guideline. 85 (62%) of the patients were in non-fibrotic form while 53 (38%) were in the fibrotic form. The most frequent etiology of our patient group was barn located under the houses in 58 (42%) patients.Conclusion: Barns under the houses in rural areas and moldy houses in urban areas are two main etiology of HP in our region. The presence of chronic form mostly in our patient group shows HP can not be diagnosed at an early stage. We propose chronic forms to classify as “chronic inflammatory” and “chronic fibrotic”. Classifying patients according to two new HP guidelines results in a very high “definite diagnosis” according to ACCP compared to ATS.